Hybrid generators‐based AC microgrid performance assessment in island mode. Issue 8 (11th June 2019) - Issa, Walid; Sharkh, Suleiman; Abusara, Mohammad
Abstract : Achieving an accurate steady‐state averaged active power sharing between parallel inverters in islanded AC microgrids could be realised by a traditional droop control. For identical inverters having the same droop gains, it is assumed that the transient average power responses will be similar, and no circulating current will flow between the units. However, different line impedances could influence the instantaneous power significantly and thus circulating power flows among the inverters particularly during sudden disturbances such as load changes. This power, if absorbed by an inverter, will lead the DC link voltage to rise abruptly and trip the inverter, thus, degrading the performance of the whole microgrid. The problem becomes worse when hybrid generators are serving as a unidirectional power source. This study assesses the performance of hybrid generators within an islanded microgrid against the mismatch in line impedances. Two schemes to stabilise the microgrid are proposed. In addition, a participation factor analysis is developed to select the most effective controller scheme to bound the DC link voltage and minimise the circulating power. Simulation and experimental results are presented to verify the analysis and the capability of the proposed controller.